Computational morphology design of duplex structure considering interface debonding - Zhou, Jiaxin; Watanabe, Ikumu; Yamada, Takayuki (Composite structures, 2022)
A finite volume interface is an interface region with interface strength, and is most often generated during the fabrication (3D printing) of a duplex structure. However, it is often neglected in morphology design due to numerical complexity and computational difficulties. In addition, a sharp and perfect-bonding interface is usually assumed in literatures. However, such assumptions bring failure risks, thus limiting the industrial applicability of the morphology designs of duplex structures. This study aims to identify the optimal morphology design though a computational design method, considering the finite volume interface and debonding of a duplex structure. This method is based on topology optimization, which utilizes a level-set function for optimizing material distribution in the design space. To introduce finite volume interfaces in morphology design, a simple interface debonding model is integrated into implicit finite element analysis, based on the finite strain theory. Moreover, a distance function is employed to describe the interface region in addition to a level-set function for topology optimization. Further, a topological derivative based on an adjoint variable method is formulated for a debonding interface state in a nonlinear finite element analysis, which is incorporated in topology optimization to obtain the optimal duplex structures. The numerical demonstrations verified the applicability of the proposed approach. The zigzag interface was proven to be one of the features of the optimal duplex structures, considering interface debonding. The results also indicated the optimal duplex structures considering interface debonding to be non-symmetric, in which the interfaces are primarily enriched in compression areas to ensure structural integrity. [Display omitted] •Nonlinear topology optimization considering finite volume interface is proposed.•Nonlinear finite element analysis at finite strain with simple interface modeling is proposed.•Combined distance and level-set functions to generate a duplex structure with interface thickness.•Demonstrated finite strain and interface effect on duplex design.